Paclitaxel and curcumin co-loaded mixed micelles. Improving in vitro efficacy and reducing toxicity against Abraxane® - Calabró López, María Valeria; Bernabeu, Ezequiel Adrián; Riedel, Jennifer Denise; Lázaro-Martínez, Juan Manuel; Prieto, María Jimena; González, Lorena; Martínez, Carolina Soledad; Alonso, Silvia del Valle; Evelson, Pablo; Chiappetta, Diego Andrés; Moretton, Marcela Analía (Elsevier, 2021)
Vismodegib is a first-in-class inhibitor for advanced basal cell carcinoma treatment. Its dailyoral doses present a high distribution volume and several side effects. We evaluated its skin penetration loaded in diverse nanosystems as potential strategies to reduce side effects and drug quantities. Ultradeformable liposomes, ethosomes, colloidal liquid crystals, and dendrimers were able to transport Vismodegib to deep skin layers, while polymeric micelles failed at this. As lipidic systems were the most effective, we assessed the in vitro and in vivo toxicity of Vismodegib-loaded ultradeformable liposomes, apoptosis, and cellular uptake. Vismodegib emerges as a versatile drug that can be loaded in several delivery systems for topical application. These findings may be also useful for the consideration of topical delivery of other drugs with a low water solubility.
Keywords: Ingeniería y tecnología::Nano-tecnología